A choice-based approach to the measurement of inflation expectations - Goldfayn-Frank, Olga; Kieren, Pascal; Trautmann, Stefan T. (AWI discussion paper series, 2024)
In macroeconomic surveys, inflation expectations are commonly elicited via density forecasts in which respondents assign probabilities to pre-specified ranges in inflation. This question format is increasingly subject to criticism. In this study, we propose a new method to elicit inflation expectations which is based on prior decision theoretic research. We demonstrate that it leads to well-defined expectations with central tendencies close to the corresponding point forecasts and to lower forecast uncertainty than density forecasts. In contrast to currently employed methods, the approach is robust to differences in the state of the economy and thus allows comparisons across time and across countries. Additionally, the method is not very time consuming and portable in the sense that it can be applied to different macroeconomic measures.
Keywords: Graue Literatur